Roles of Hormones in Elevated pH-Mediated Mitigation of Copper Toxicity in Citrus sinensis Revealed by Targeted Metabolome - Jiang Zhang; Wei-Lin Huang; Wei-Tao Huang; Xu-Feng Chen; Huan-Huan Chen; Xin Ye; Lin-Tong Yang; Li-Song Chen (Plants, 2023)
The effects of copper (Cu)–pH interactions on the levels of hormones and related metabolites (HRMs) in Citrus sinensis leaves and roots were investigated. Our findings indicated that increased pH mitigated Cu toxicity-induced alterations of HRMs, and Cu toxicity increased low-pH-induced alterations of HRMs. Increased pH-mediated decreases in ABA, jasmonates, gibberellins, and cytokinins, increases in (±)strigol and 1-aminocyclopropanecarboxylic acid, and efficient maintenance of salicylates and auxins homeostasis in 300 μM Cu-treated roots (RCu300); as well as efficient maintenance of hormone homeostasis in 300 μM Cu-treated leaves (LCu300) might contribute to improved leaf and root growth. The upregulation of auxins (IAA), cytokinins, gibberellins, ABA, and salicylates in pH 3.0 + 300 μM Cu-treated leaves (P3CL) vs. pH 3.0 + 0.5 μM Cu-treated leaves (P3L) and pH 3.0 + 300 μM Cu-treated roots (P3CR) vs. pH 3.0 + 0.5 μM Cu-treated roots (P3R) might be an adaptive response to Cu toxicity, so as to cope with the increased need for reactive oxygen species and Cu detoxification in LCu300 and RCu300. Increased accumulation of stress-related hormones (jasmonates and ABA) in P3CL vs. P3L and P3CR vs. P3R might reduce photosynthesis and accumulation of dry matter, and trigger leaf and root senescence, thereby inhibiting their growth.